Main Character’s Inner Conflict in Brian Khrisna’s Kudasai: Freudian Psychoanalysis - Ferdiansyah, Rafi; Sa'adah, Sufi Ikrima (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2022)
This article aims to portray the inner conflict that Chaka, the main character in Brian Khrisna Kudasai, experienced. Chaka’s decision to leave his girlfriend and marry another woman caused him a strong regret leading to inner conflict when he meets the long-lost lover. The unexpected meeting put Chaka into a dilemma of choosing the past or maintaining the present. This study employs a psychological approach with Freudian psychoanalysis as the theoretical basis. With the descriptive qualitative method, the analysis maps the cause, the conflict point, and the effect on Chaka’s life. Chaka underwent an inner conflict due to his decision to leave Anet, his girlfriend, to marry Twindy. The conflict reaches its point when Chaka faces two choices: being with the dying Anet or the pregnant Twindy. Chaka’s failure to resolve his inner conflict causes him deep depression ending with his death.